The Early Life History Transitions of the Bivalve Aulacomya atra From the Humboldt Current System Off Peru Are Affected by Human Exploitation and Modulated by El Niño–La Niña Cycle - Solís, Marco A.; Ballesteros, Manuel; Riascos, José M. (Frontiers in Marine Science, 2019)
Understanding the factors and mechanisms that control temporal changes of larval settlement and subsequent recruitment of marine bivalves have strong implications for the management of exploited populations of coastal species and the conservation of benthic communities. Therefore, assessing both organismal and environmental drivers of the reproductive function, gamete release and recruitment is important. This is particularly true for highly productive upwelling coastal areas that are heavily affected by shifts in climatic regimes during the El Niño (EN)-La Niña (LN) cycle. We aimed to assess temporal variation in the transition between gamete release, larval settlement and subsequent recruitment of the commercially important ribbed mussel (Aulacomya atra) at Bahía Independencia (Peru) over nine years (1996-2004)—a period that covered strong EN and LN episodes. We also evaluate the environmental factors implied in these changes. To achieve this, we monitored monthly changes of the spawning stock biomass (SSB; a proxy of the capacity for propagule production and release), the number of settled postlarvae on artificial collectors, the density of recruits of A. atra and several environmental parameters. Our results showed a persistent trend of decreasing SSB and recruitment density, most likely related to human exploitation that reduced the population density by one order of magnitude. The SSB was a significant predictor of the number of settled postlarvae, regardless of the occurrence of EN or LN episodes. In contrast, the relationship between SSB and the density of recruits was dependent on the occurrence of EN or LN. The SSB and the larval settlement were heavily reduced during the warm EN in 1997-1998, presumably as a typical response of species of Antarctic origin to warmer-nutrient depleted waters and disturbed circulation patterns within the bay that may favor offshore transport of larvae. Despite this, the density of recruits of A. atra was high during EN, presumably as a result of reduced competition for food and reduced predation, which may overcompensate for the mortality of recruits associated with thermal stress.